Bridge Pier Design in the Digital Age: Leveraging Revit for Efficient Design and Analysis - Jason Budiono; Susanty Handayani; Joewono Prasetijo (LEADER: Civil Engineering and Architecture Journal, 2025)
This research explores integrating Building Information Modeling (BIM) technology, specifically Autodesk Revit, into the bridge piers' design and planning process. The authors emphasize the pivotal role of technology in the advancement of infrastructure, with a focus on Indonesia's extensive toll road projects and the Barelang bridge as a prime example of sustainable infrastructure development. The transitions from AutoCAD to BIM in the construction industry are discussed, with BIM being recognized for increasing efficiency and accuracy in construction projects. The authors acknowledge the obstacles to BIM adoption, including substantial upfront costs and limited technological progress, but also highlight the potential for considerable cost savings in material procurement and building projects. Autodesk Revit is identified as a prominent BIM-based program that offers detailed 3D models, drawings, and schedules, enabling construction stakeholders to collaborate effectively. In conclusion, the document calls for adopting BIM and BrIM in the AEC sector, suggesting that these technologies can streamline bridge design and maintenance, contributing to more sustainable and cost-effective infrastructure.